2000
DOI: 10.1107/s0907444999015334
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure and structural transition of the α-helical capsid in filamentous bacteriophage Pf1

Abstract: The major coat protein in the capsid of Pf1 ®lamentous bacteriophage (Inovirus) forms a helical assembly of about 7000 identical protein subunits, each of which contains 46 amino-acid residues and can be closely approximated by a single gently curved -helix. Since the viral DNA occupies the core of the tubular capsid and appears to make no signi®cant speci®c interactions with the capsid proteins, the capsid is a simple model system for the study of the static and dynamic properties of -helix assembly. The caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 42 publications
3
54
1
Order By: Relevance
“…Structural fitting 21 of assigned experimental NMR data yields a unique three-dimensional structure of the protein. For the Pf1 coat protein structure described here (PDB entry 1PJF), the effective resolution determined by taking into account all sources of experimental error and uncertainties in the spin interaction tensors is estimated to be 1.5 Å , which compares favorably to the values reported for the structures determined by X-ray 5 fiber and neutron 7,8 diffraction. At atomic resolution, the structure of Pf1 coat protein is remarkably complex.…”
supporting
confidence: 56%
“…Structural fitting 21 of assigned experimental NMR data yields a unique three-dimensional structure of the protein. For the Pf1 coat protein structure described here (PDB entry 1PJF), the effective resolution determined by taking into account all sources of experimental error and uncertainties in the spin interaction tensors is estimated to be 1.5 Å , which compares favorably to the values reported for the structures determined by X-ray 5 fiber and neutron 7,8 diffraction. At atomic resolution, the structure of Pf1 coat protein is remarkably complex.…”
supporting
confidence: 56%
“…Anti-Pf4 polyclonal antibodies were developed by using a synthetic peptide (Auspep, Parkville, Australia) with the following amino acid sequence: Gly-Val-Ile-Asp-Thr-Ser-Ala-Val-GluSer-Ala-Ile-Thr-Asp-Gly-Cys. This sequence corresponds to residues 1 to 15 of CoaB (PA0723; the major coat protein of the filamentous phage virion) of Pf1 (and of Pf4), which is exposed on the outer surface of the bacteriophage virion (35,61). An extra cysteine residue was added to the N terminus of this peptide for coupling to the carrier protein, keyhole limpet hemocyanin.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the calorimetry data, Hinz et al (18) hypothesized that one or more hydrophobic side chains change positions to lower their surface contact with water. Welsh et al (11), to account for their proposed conversion of a monomeric asymmetric unit in Pf1 L to a trimeric asymmetric unit in Pf1 H , suggested more extensive changes in subunit contacts and structure on the basis of proposed similarities to molecular crystals.…”
Section: Locations Of Atoms With Perturbed Chemical Shifts On Hydrophmentioning
confidence: 99%
“…One difference between Pf1 and the others that might account for the presence of a transition in Pf1 and not the others is its 1:1 stoichiometry. Diffraction studies of oriented phage in solution showed that the low and high temperature forms differ slightly in the orientation of the subunit with respect to the filament axis (10,11). The two states have slightly different numbers of subunits per turn in the helical arrangement of their capsids, which produce very different diffraction patterns even though the structures are closely similar.…”
mentioning
confidence: 99%